2018
DOI: 10.1002/lio2.210
|View full text |Cite
|
Sign up to set email alerts
|

Elongated EABR wave latencies observed in patients with auditory neuropathy caused by OTOF mutation

Abstract: ObjectivesWe sought to determine how the pathology altered electrically evoked auditory brainstem responses (EABRs) in patients with hearing loss by evaluating EABRs in auditory neuropathy patients with OTOF mutations comparing with various types of congenital deafness.MethodsWe included 15 patients with congenital hearing loss, grouped according to pathology: OTOF mutations (n = 4), GJB2 mutations (n = 4), SLC26A4 mutations (n = 4), or cytomegalovirus infections (n = 3). EABRs were recorded when patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
(86 reference statements)
1
9
0
Order By: Relevance
“…Indeed, wave III and wave V latencies obtained from cochlear implantees carrying the OTOF variants were significantly longer than those carrying the GJB2 or SLC26A4 variants, suggesting that postsynaptic (central to the SGNs) activity, such as CN synchrony, was still disturbed after implantation in DFNB9 subjects [ 21 ]. It was proposed that the prolonged disturbance in postsynaptic synchrony could be caused by insufficient presynaptic stimulation and/or delayed maturation of the nervous system, including both pre- and post-synaptic neuronal networks [ 21 ]. Collectively, earlier intervention could be crucial to auditory cortical maturation and successful behavioral outcomes of CI in subjects with OTOF variants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, wave III and wave V latencies obtained from cochlear implantees carrying the OTOF variants were significantly longer than those carrying the GJB2 or SLC26A4 variants, suggesting that postsynaptic (central to the SGNs) activity, such as CN synchrony, was still disturbed after implantation in DFNB9 subjects [ 21 ]. It was proposed that the prolonged disturbance in postsynaptic synchrony could be caused by insufficient presynaptic stimulation and/or delayed maturation of the nervous system, including both pre- and post-synaptic neuronal networks [ 21 ]. Collectively, earlier intervention could be crucial to auditory cortical maturation and successful behavioral outcomes of CI in subjects with OTOF variants.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that ANSD shows obvious heterogeneity, not only in the etiologies, but also in the amount of stimulus required for auditory cortical maturation. Recently, as evidenced by the electrically evoked ABR, OTOF variants were more closely associated with delayed postsynaptic neurotransmission [ 21 ]. The mechanism of peripheral neural dyssynchrony due to alteration of OTOF , which has been reported to be expressed exclusively in the IHC and affects the synapse between the IHCs and SGNs, can influence maturation of the auditory cortex requires further research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, previous studies suggested that the sensitive period for successful CI outcomes for children with OTOF -related DFNB9 may be narrower than that for those with SLC26A4 - and GJB2 -related deafness [ 14 , 33 ]. Supporting this, abnormal cortical auditory evoked potentials and delayed postsynaptic neurotransmission in children with ANSD may reflect abnormal maturation of the central auditory system, necessitating early intervention [ 34 , 35 ]. Collectively, OTOF -related DFNB9 with early intervention, i.e., before the age of 24 months, is considered a good candidate for CI with a good prognosis for outcome.…”
Section: Discussionmentioning
confidence: 99%